2010
DOI: 10.1021/ci9004892
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Evaluation of Residue and Protein Volumes by Means of Laguerre Tessellation

Abstract: Amino acids control the protein folding process and maintain its functional fold. This study underlines the interest of the Laguerre tessellation to determine relevant amino acid volumes in proteins. Previous studies used a limited number of proteins and only buried residues. The present computations improve the method and results on three main points: (i) a large, high-quality updated and refined data bank of proteins is used; (ii) all residues are taken into account, including those at the protein surface, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(70 citation statements)
references
References 73 publications
3
65
0
Order By: Relevance
“…In a previous work (8), we showed that computations based on tessellations gave a good agreement with experimental results in the evaluation of amino acid volumes, better than the other equivalent methodologies.…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations
“…In a previous work (8), we showed that computations based on tessellations gave a good agreement with experimental results in the evaluation of amino acid volumes, better than the other equivalent methodologies.…”
Section: Introductionmentioning
confidence: 53%
“…It allows us to take into account all the residues, including the accessible ones at the protein surface. In a previous work (8), we showed that computations based on tessellations gave a good agreement with experimental results in the evaluation of amino acid volumes, better than the other equivalent methodologies.The protein contacts are a crucial feature to analyse protein structures. The usual definition is based only on geometrical parameters, such as distance-threshold (18), and used for instance to identify small compact units (protein units) (19–21).…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Steric clashes are a straightforward and sensitive measure of overpacking, but underpacking is more difficult. Although methods exist for identifying cavities, for instance using Voronoi or related volume concepts [38], none have provided practical diagnostics adopted into validation. RosettaHoles [39] is a less mathematically elegant but more practical system of filtered overlapping spheres.…”
Section: Current Developments (2009-2013)mentioning
confidence: 99%